2022
DOI: 10.3390/pathogens11010073
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Polymer Nanoparticles Show Efficacy against Candida Species Biofilms

Abstract: Purpose: Chronic infections of Candida albicans are characterised by the embedding of budding and entwined filamentous fungal cells into biofilms. The biofilms are refractory to many drugs and Candida biofilms are associated with ocular fungal infections. The objective was to test the activity of nanoparticulate amphotericin B (AmB) against Candida biofilms. Methods: AmB was encapsulated in the Molecular Envelope Technology (MET, N-palmitoyl-N-monomethyl-N,N-dimethyl-N,N,N-trimethyl-6-O-glycolchitosan) nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…[30,31] Another study from Alakkad et al, 2022 demonstrated powerful antifungal activity against biofilm-embedded (Candida albicans) cells. [32,33] These data indicated that the new formulation of Am-B (encapsulated in the Molecular Envelope Technology; N-palmitoyl-N-monomethyl-N, N-dimethyl-N,N,N-trimethyl-6-O-glycolchitosan) has a more antifungal activity compared to the drug alone in Candida biofilms. [33] These data indicated that a new formulation of Am-B can be more effective with minimal cytotoxicity for living cells.…”
Section: Polymeric/protein Nanostructured Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[30,31] Another study from Alakkad et al, 2022 demonstrated powerful antifungal activity against biofilm-embedded (Candida albicans) cells. [32,33] These data indicated that the new formulation of Am-B (encapsulated in the Molecular Envelope Technology; N-palmitoyl-N-monomethyl-N, N-dimethyl-N,N,N-trimethyl-6-O-glycolchitosan) has a more antifungal activity compared to the drug alone in Candida biofilms. [33] These data indicated that a new formulation of Am-B can be more effective with minimal cytotoxicity for living cells.…”
Section: Polymeric/protein Nanostructured Particlesmentioning
confidence: 99%
“…[ 30,31 ] Another study from Alakkad et al., 2022 demonstrated powerful antifungal activity against biofilm‐embedded ( Candida albicans ) cells. [ 32,33 ] These data indicated that the new formulation of Am‐B (encapsulated in the Molecular Envelope Technology; N ‐palmitoyl‐ N ‐monomethyl‐ N , N ‐dimethyl‐ N , N , N ‐trimethyl‐6‐ O ‐glycolchitosan) has a more antifungal activity compared to the drug alone in Candida biofilms. [ 33 ] These data indicated that a new formulation of Am‐B can be more effective with minimal cytotoxicity for living cells.…”
Section: Polymeric/protein Nanostructured Particlesmentioning
confidence: 99%
“…Polymeric NPs are nanosized particles composed of polymeric materials . The PNPs have numerous benefits over conventional antimicrobial agents, including enhanced drug stability, bioavailability, solubility, and sustained release. , They have also been extensively investigated for their anti-biofilm and antibacterial activity . Polymeric NPs can be prepared using several techniques such as solvent evaporation, emulsion, and nanoprecipitation.…”
Section: Nanotechnological Approaches For Biofilm Controlmentioning
confidence: 99%
“…Amphotericin B (AmB) polymeric NPs showed efficacy against Candida biofilms on polystyrene surfaces. Results showed that the polymeric NPs were ∼30× more efficient than AmB alone . Arias-Moliz and colleague showed that E. faecalis ATCC 29212 biofilms were inhibited by doxycycline-functionalized polymeric NPs on dentine material .…”
Section: Nanotechnological Approaches For Biofilm Controlmentioning
confidence: 99%
“…Although oral NPs resulted in lower AmB levels compared to intravenous liposomes in tested organs, they displayed similar efficacy in treatment of visceral leishmaniasis, aspergillosis, and systemic candidiasis in animal models ( Serrano et al., 2015 ). This formulation also exhibited increased anti-biofilm efficiency for better penetration ( Alakkad et al., 2022 ). Despite the massive designs in drug delivery systems, only a few studies have presented results of in vivo testing.…”
Section: Polymer-based Strategies In Fungal Disease Treatmentmentioning
confidence: 99%